High aspect ratio nanomaterial-induced macrophage polarization is mediated by changes in miRNA levels - Erdem, Johanna Samulin; Závodná, Táňa; Ervik, Torunn K.; Skare, Øivind; Hron, Tomáš; Anmarkrud, Kristine H.; Kuśnierczyk, Anna; Catalán, Julia; Ellingsen, Dag G.; Topinka, Jan; Zienolddiny-Narui, Shan (Frontiers in Immunology, 2023)
Inhalation of nanomaterials may induce inflammation in the lung which if left unresolved can manifest in pulmonary fibrosis. In these processes, alveolar macrophages have an essential role and timely modulation of the macrophage phenotype is imperative in the onset and resolution of inflammatory responses. In this study, the immunomodulating effects of two classes of industrially relevant high aspect ratio nanomaterials, namely nanocellulose (NC) and multiwalled carbon nanotubes (MWCNT), and the involvement of epigenetic regulation were investigated in an air-lifted alveolar macrophage model. Our data illustrate that both nanomaterials trigger phenotypic changes in alveolar macrophages, where NC exposure leads to enhanced M1 phenotype and MWCNT promotes M2 phenotype. In accordance, MWCNT-induced M2 phenotype involved more prominent epigenetic regulatory events with changes in the expression of histone modification and DNA methylation enzymes as well as in miRNA transcript levels. MWCNT-enhanced changes in the macrophage phenotype involved prominent downregulation of the histone methyltransferases Kmt2a and Smyd5 and histone deacetylases Hdac4, Hdac9 and Sirt1 indicating that both histone methylation and acetylation events may be critical in the Th2 responses to MWCNT. Furthermore, MWCNT as well as NC exposure led to altered miRNA levels, where miR-155-5p, miR-16-1-3p, miR25-3p, and miR-27a-5p were significantly regulated by both materials. PANTHER pathway analysis of the identified miRNA targets showed that both materials affected growth factor (PDGF, EGF and FGF), Ras/MAPKs, CCKR, GnRH-R, integrin, and endothelin signaling pathways. These pathways are important in inflammation or in the activation, polarization, migration, and regulation of phagocytic capacity of macrophages. In addition, pathways involved in interleukin, WNT and TGFB signaling were highly enriched following MWCNT exposure. Altogether, these data support the importance of macrophage phenotypic changes in the onset and resolution of inflammation and identify epigenetic patterns in macrophages which may be critical in nanomaterial-induced inflammation and fibrosis.